EGB-promoted electrochemical synthesis of 6-thioxo-[1, 3, 5]-triazinane-2, 4 dione derivatives. Issue 8 (17th April 2016) - Sbei, Najoua; Haouas, Baya; Boujlel, Khaled; Batanero, Belen; Benkhoud, Mohamed Lamine
ABSTRACT: A simple method for the synthesis of 6-thioxo-[1, 3, 5]-triazinane-2, 4-dione derivatives was reported. The electrogenerated cyanomethyl base obtained from electroreduction of neat acetonitrile assisted the reaction between thiourea derivatives and alkyl or aryl isocyanate. This protocol had the advantage of giving good yields using mild conditions. The obtained products have been identified by spectroscopic data, mass spectrometry, and high-resolution mass spectra or elemental analysis. GRAPHICAL ABSTRACT: